Legal Certainty in the Regulation of Hate Speech: A Comparative Study of Indonesia and Germany - Leksono, Avivah Firisqi; Rohmana, Vivi (Universitas Islam Negeri Sumatera Utara, 2026)
Freedom of expression is a fundamental right guaranteed by the constitution, but it is not absolute, as it may be restricted to protect human dignity, public order, and the rights of others. In Indonesia, this guarantee is enshrined in the 1945 Constitution, but at the statutory level, it remains fragmented across the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE) without clear normative criteria to distinguish between criticism and hate speech. This situation leads to multiple interpretations, legal uncertainty, and the risk of overcriminalization of public expression. This study employs a normative legal method with a comparative approach between Indonesia and Germany. The German legal system was chosen because it features an integrated normative framework through the Basic Law (Grundgesetz), §130 of the Criminal Code (Strafgesetzbuch), and the Network Enforcement Act (NetzDG), which provide more detailed indicators. The findings indicate that Germany possesses a higher level of normative precision and legal certainty. The novelty of this study lies in its comparative analysis, which integrates normative, philosophical, and implementational dimensions to formulate more precise legal indicators for limiting hate speech. Therefore, a reformulation of normative indicators in Indonesian legislation is necessary to strengthen the balance between freedom of expression and the protection of human rights in the digital age.